2009
DOI: 10.1590/s1516-89132009000300004
|View full text |Cite
|
Sign up to set email alerts
|

Mineral composition and dry mass production of the corn plants in response to phosphorus sources and aluminum concentration

Abstract: The corn plants were evaluated with different phosphate fertilizer sources and aluminum (Al)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
2
3
0
Order By: Relevance
“…Confirming our results, several authors also reported a higher ShDW of maize plants after soluble phosphate application compared with the isolated application of rock phosphates, such as Arad (Batista et al 2009) or Gafsa (Franzini et al 2009). On the other hand, despite the better immediate response to soluble phosphates, it should be remembered that in the long term, the residual effect of the less soluble sources may compensate for the unavailability of P during the first crops, and may be proportional to the initial gain of the soluble sources.…”
Section: Resultssupporting
confidence: 91%
“…Confirming our results, several authors also reported a higher ShDW of maize plants after soluble phosphate application compared with the isolated application of rock phosphates, such as Arad (Batista et al 2009) or Gafsa (Franzini et al 2009). On the other hand, despite the better immediate response to soluble phosphates, it should be remembered that in the long term, the residual effect of the less soluble sources may compensate for the unavailability of P during the first crops, and may be proportional to the initial gain of the soluble sources.…”
Section: Resultssupporting
confidence: 91%
“…Similarly, 57.5% reduction in the shoot dry weight was observed in a Nigerian Dura x Nigerian Dura oil palm progeny (Christancho et al, 2011). Reduction in the shoot's dry mass of corn plants was also observed when the plants were treated with 100 mg kg -1 Al (Batista et al, 2009). In the present study, K content in the roots of Elite Deli Dura x BM119 AVROS Pisifera seedlings decreased upon exposure to Al concentrations of 200 and 300 µM.…”
Section: Discussionsupporting
confidence: 68%
“…This positive effect can be correlated with the availability of P in the root. Increasing P availability in the root cell protects the cell membrane against Al toxic actions (Batista et al, 2009). Decreasing root and shoot biomass was correlated with the reduction of root and shoot growth.…”
Section: Discussionmentioning
confidence: 93%
“…In maize, a reduction was observed in the dry mass of the aerial part with increase of aluminum (Batista et al, 2009). Although showing less development, based on these characteristics, cultivar Catuaí Amarelo IAC 62 was the only one that effectively presented primary root growth increase (Table 3), indicating its tolerance to aluminum.…”
Section: Resultsmentioning
confidence: 97%